Policies regarding use of ICT in education - Cristian USCATU (Informatică economică, 2006)
Use of ICT in education comes naturally with the trend of technology and society evolution. The appeal of these technologies made them a point of interest for policy makers around the globe. National, regional and world policies now include chapters dedicated to integrating ICT in education and moving education more and more to the internet and the virtual electronic realm. This paper reviews some of the main political trends regarding the use of ICT in education in Europe, Romania, Japan ad on the world scale (UNESCO).